2006
DOI: 10.1002/ajh.20646
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high-dose therapy and hematopoietic stem cell transplantation for mantle cell lymphoma

Abstract: Conventional treatment of mantle cell lymphoma (MCL) yields modest responses and short remissions. We report 30 hematopoietic stem cell transplants (HSCT) for MCL: 13 autologous, 10 allogeneic myeloablative, and 7 nonablative. After a median 1.2 years from diagnosis (range 0.5 to 4.7) and a median of 2 pre-HSCT chemotherapeutic regimens (range 1 to 5), their median age at HSCT was 52 years (range 37 to 67). Eleven patients (41%) were in first remission, 11 (41%) were in second remission, and 7 (25%) had resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Since all but one patient received similar myeloablative transplant conditioning regimens (cyclophosphamide plus either TBI or busulfan), the differences seen are most likely attributable to the effects and complications of an engrafted donor immune system. Similar results were seen in a smaller retrospective study from the University of Minnesota [13]. In this study, the majority of patients who received autoHCT (n = 13) were in first remission, whereas the majority of those treated with alloHCT (n = 17) had relapsed or refractory disease, including 3 patients that had relapsed following autoHCT.…”
Section: Comparison Of Autologous Vs Allogeneic Hct In MCLsupporting
confidence: 86%
“…Since all but one patient received similar myeloablative transplant conditioning regimens (cyclophosphamide plus either TBI or busulfan), the differences seen are most likely attributable to the effects and complications of an engrafted donor immune system. Similar results were seen in a smaller retrospective study from the University of Minnesota [13]. In this study, the majority of patients who received autoHCT (n = 13) were in first remission, whereas the majority of those treated with alloHCT (n = 17) had relapsed or refractory disease, including 3 patients that had relapsed following autoHCT.…”
Section: Comparison Of Autologous Vs Allogeneic Hct In MCLsupporting
confidence: 86%
“…All of these small studies were characterized by selected, young patients (median age typically b 50 years), the use of a HLA-matched sibling donors, and unmodified grafts (with the exception of one study) [62][63][64][65][66][67][68][69]. These early studies demonstrated OS of 40-50% at 4 years in highly selected patient cohorts.…”
Section: From Myeloablative To Reduced Intensity Conditioning Regimensmentioning
confidence: 99%
“…Despite recent progress in conventional treatment, allogeneic hematopoietic cell transplantation (HCT) remains the only potentially curative treatment option for patients with mantle cell lymphoma (MCL). Initially, allogeneic HCT was attempted in these patients with high‐dose myeloablative regimens, but concerns about the relatively high risks for treatment‐related mortality have limited its use to younger, medically fit patients. Given that the median age of diagnosis with MCL is beyond the 6th decade, various groups have examined the feasibility of using reduced‐intensity or nonmyeloablative conditioning regimens for patients with MCL, and results have been encouraging .…”
Section: Introductionmentioning
confidence: 99%